POLICIES TO REDUCE HOME DELIVERY IN INDONESIA: WHO SHOULD BE THE TARGET? - Ratna Dwi Wulandari; Agung Dwi Laksono; Ratu Matahari; Nikmatur Rohmah (Indonesian Journal of Health Administration, 2023)
Introduction: Home delivery increases the chance of maternal death. Aims: The study examines suitable targets for developing policies to reduce home births. Methods: This cross-sectional study analyzed 15,357 mothers through stratification and multistage random sampling, including 13 independent variables: age, education, employment, marital, parity, insurance, knowledge of pregnancy danger signs, antenatal care (ANC), residence, the autonomy of health and family finance, household head sex, and wealth. We examined the data using binary logistic regression. Results: About 23.8% of mothers deliver at home. Older age, higher education, primiparous, insured, knowing the pregnancy danger signs, living in an urban area, and doing ANC ≥4 times were protective factors to not home delivery. Being employed, married, having a male household head, and being poor were risk factors for home delivery. Mothers without health autonomy are less likely to deliver at home than those with health autonomy. Mothers with family finance autonomy are 1.239 times more likely than those without to give home birth. Conclusion: The target to reduce home deliveries: young, low education, employed, married or divorced/widowed, having many children, uninsured, do not know pregnancy danger signs, doing ANC <4 times, living in a rural area, have no health autonomy, have no family finance autonomy, having a male household head, and poor. Keywords: big data, home delivery, maternal health, maternity care, population health, public health.